(untitled) (Journal of Philosophy Culture and Political Science, 2018)
The article analyzes the problems of society`s urbanization and marginalization in the context of globalization, socio-political and intercultural processes intensification. At this stage of civilizational development, modern Kazakhstan faces a number of problems, from the solution of which the future depends. The geographical location of the Republic of Kazakhstan, the influence of the West and the East cultures and the population`s polyethnic composition actualizes issues of ethnic, national, cultural and civilized identity. The republic`s independent existence strengthens the tendency of Kazakh ethnos to recurrence of cultural heritage. At the same time, foreign models of the Western European thinking type, which came with the introduction of the West economic systems, are actively implanted. In this regard, the phenomenon of multilingualism is viewed as a problem of urban society, which is always polyethnic, with a complex network of social norms and values. Key words: culture, globalization, marginality, acculturation, assimilation.